HUBUNGAN ANTARA KEPEMIMPINAN VISIONER KEPALA SEKOLAH DENGAN PEMBENTUKAN KARAKTER DISIPLIN GURU - Ivon Mukaddamah; Urwatul Wutsqah (Sekolah Tinggi Pariwisata Mataram, 2022)
This study intends to analyze the relationship between the visionary leadership of Headmaster whit the labour of discipline teachers on Islamic state junior hight school teachers in west java. The raseach was conducted in Islamic junior high school, west java and using survey methods. Target population in this study a special civil servant teachers as many as 188 people and the affordable population as many as 126 people. By using the slovin formula to determine the population at affordable so that the teachers sampled were 95 people. In determining the sample the authers use a multi stage proposional simple random sampling. For the result of research can be concluded matters as follows: there is positive relationship between the visionary leadership of headmaster (X) whit the labour of discipline teachers ( Y )with regression equation Y=4,71+0,87X1, with correlation coefficient ry1 = 0,97 and the coefficient of determination (D) = (ry1)2 = 0,9409 significant at a=0,05.